Effects of Dietary Taurine and Gamma Aminobutyric Acid on the Steroil CoA Desaturase and ?6, 5 Desaturase Enzyme Activities in Liver Tissues of Rats - Ozkan, Yusuf; Yilmaz, Oekkes; Tuzcu, Mehmet; Murat, Gulsen; Guvenc, Mehmet; Ozturk, Ali Ihsan; Şahin, Kazım (Medwell Online, 2008)
In this study, the effects of dietary taurine (2-amino ethane sulphonic acid) (TAUR) and Gamma Amino Butyric Acid (GABA) on the levels of reduced glutathione (GSH), lipid and fatty acid composition in liver tissues of 3 and 8 months female wistar rats was evaluated. The rats (n = 48) were randomly assigned to 8 treatment groups consisting of 6 rats each. The rats (both 3 and 8 month old) were fed a basal diet (Control) or basal diet plus taurine given by drinking water (500 mg kg(-1)) (TAUR groups) or basal diet plus GABA given by drinking water (500 mg kg(-1)) (GABA) or basal diet plus the combinations of GABA and TAUR given by drinking water (500 + 500 mg kg(-1)) (GABA+TAUR groups). In 3 month old rats, the lipid level in GABA and GABA+TAUR groups was higher than control group (p<0.01). GSH level was high in the TAUR group (p<0.05). While, the lipid level increased in GABA group of 8 month old rats, its level decreased in TAUR group (p<0.05). The level of GSH in GABA, TAUR and GABA+TAUR groups was lower than control group (p<0.01). Oleic acid level (18: 1, n-9) was high in TAUR group (p<0.05) and linoleic acid level (18:2, n-6) GABA and GABA+TAUR groups was higher than control group (p<0.01) in 3 month old rats. However, arachidonic acid level (20:4, n-6) in supplemented groups was lower than control group (p<0.01). While, the saturated fatty acid level increased in the supplemented groups, unsaturated fatty acid decreased in the same groups (p<0.05). In 8 month old rats, palmitic acid level (16:0) increased in supplemented groups (p <= 0.05), but stearic acid level decreased in the same groups. The levels of oleic and linoleic acids were high in GABA and GABA+TAUR groups. Arachidonic and docosahexaenoic acid levels in GABA and GABA+TAUR groups were lower than control group (p<0.01). The level of saturated fatty acid level was high in the GABA and TAUR groups, but the unsaturated fatty acid was low in the same groups (p<0.05). In conclusion, present study showed that the products of Delta 6 desaturation pathway such as arachidonic acid was decreased by the GABA and taurine in 3 and 8 months old of female rats. Conversely, the products of steroil CoA desaturase were increased by dietary taurine treatment.
Keywords: Taurine; gamma amino butyric acid; lipid; GSH; cholesterol; fatty acids